Pilihan Tempat Belanja Masyarakat Perkotaan Dan Implikasinya Pada Peternak Ayam Petelur Di Perdesaan - Dewi, Ni Made Ratih Kusuma; Sukadana, I Wayan; Ayuningsasi, Anak Agung Ketut (Jurnal Ekonomi Kuantitatif Terapan, 2017)
The increasing prosperity of urban communities in Denpasar, responded by an increasing number of supermarkets and other modern food retailers has raised concerns about its negative impact on traditional retailers. In this paper we discuss about the choice pattern of public spending in the city of Denpasar in an increasingly demanding era of high quality standards. This paper also tries to explain how higher welfare of urban communities can also be distributed to farmers / ranchers in rural areas. This paper surveyed the urban community in Denpasar City to find out the choice of the shopping place for egg products. The results of the analysis using Multinomial Logit found that most people in Denpasar still shop at traditional markets and stalls for low-income and middle-income household, but some high-income household tend to shop in the modern market because they have higher quality compared to with traditional markets. People with higher education and younger household tend to shop in the modern market. Based on the choice of shopping place then we can conclude that the farmers/ranchers get a positive influence of increasing welfare in the city, because farmers/ranchers are only able to distribute their products to traditional markets, small shops and stalls.
Keywords: demand for food; supermarket; farmers; ranchers